2021
DOI: 10.1186/s12958-021-00822-0
|View full text |Cite
|
Sign up to set email alerts
|

Higher preconceptional maternal body mass index is associated with faster early preimplantation embryonic development: the Rotterdam periconception cohort

Abstract: Background Overweight and obesity affect millions of people globally, which has also serious implications for reproduction. For example, treatment outcomes after in vitro fertilisation (IVF) are worse in women with a high body mass index (BMI). However, the impact of maternal BMI on embryo quality is inconclusive. Our main aim is to study associations between preconceptional maternal BMI and morphokinetic parameters of preimplantation embryos and predicted implantation potential. In addition, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 68 publications
(62 reference statements)
0
5
0
Order By: Relevance
“…The authors found that female and male BMI affected the abortion rate and the LBR in IVF and ICSI cycles (16). Among the embryos after ICSI cultured in the time-lapse incubator EmbryoScope, higher maternal BMI is associated with faster early pre-implantation development (17). In addition, women with obesity experience a higher rate of miscarriage after euploid embryo transfer than women with a normal weight, suggesting that mechanisms other than aneuploidy are responsible for this outcome (18).…”
Section: Discussionmentioning
confidence: 99%
“…The authors found that female and male BMI affected the abortion rate and the LBR in IVF and ICSI cycles (16). Among the embryos after ICSI cultured in the time-lapse incubator EmbryoScope, higher maternal BMI is associated with faster early pre-implantation development (17). In addition, women with obesity experience a higher rate of miscarriage after euploid embryo transfer than women with a normal weight, suggesting that mechanisms other than aneuploidy are responsible for this outcome (18).…”
Section: Discussionmentioning
confidence: 99%
“…A significant rise in euploid miscarriage in obese women implies that endometrial variables are involved in weaker IVF consequences in obese women. A greater body mass index (BMI) is linked to a decreased fertilization possibility [13]. There is really growing recognition of deficient embryo implantation in obese IVF patient populations [14].…”
Section: Obesity's Influence On the Endometriummentioning
confidence: 99%
“…Van Duijn et al [2] 268 couples Maternal (adjusted for paternal BMI) Weight and height measured Maternal BMI negatively associated with tPNa, tPNf and the timing of first cell cleavage (faster preimplantation development)…”
Section: Referencesmentioning
confidence: 99%